Kapapagaria Muslim-Christian brotherhood [videorecording] - Jacob, Marilou
A documentary on Muslim culture, shot in Zamboanga, Maharlika Village and the Quiapo Mosque, it takes a first step towards understanding by breaking down myths about Muslims. With interviews of Muslims and non-Muslims and an expert from the UP Institute of Islamic Studies.